A systematic conservation strategy for crop wild relatives in the Czech Republic. Issue 4 (8th February 2017) - Taylor, Nigel G.; Kell, Shelagh P.; Holubec, Vojtěch; Parra‐Quijano, Mauricio; Chobot, Karel; Maxted, Nigel
Abstract: Aim: To create a crop wild relative (CWR) conservation strategy for the Czech Republic: the first national CWR conservation strategy for Central and Eastern Europe. Location: Czech Republic. Methods: We generated a CWR checklist for the Czech Republic and then prioritized taxa, using widely adopted criteria modified with input from local experts, to create a national CWR inventory. For 204 priority CWR species, we collated 206, 760 presence records. We carried out spatial analyses to identify patterns in species richness, gaps in existing conservation actions, complementary conservation networks and collecting strategies to increase representativeness of gene bank accessions. We considered both specific and genetic conservation, using geographic and ecogeographic proxies for the latter. Results: Passive in situ conservation of CWR in the Czech Republic is comprehensive at present, with all but one priority CWR species being contained in protected areas. Active in situ CWR conservation could be focussed within 11 ca. 10‐km‐by‐10‐km grid cells containing 94% of priority species, or their overlapping protected areas. To augment the genetic coverage of the in situ conservation network, active CWR conservation is encouraged within 11 supplementary areas. Meanwhile, there are huge gaps in ex situ collections, with no known conserved material for 134 of the 204 priority species. Furthermore, existing accessions are generally unrepresentative of genetic diversity. Main conclusions: In the Czech Republic, active in situ conservation of priority CWR should be instigated within the 22 recommended grid cell areas or their 14 overlapping protected areas. For ex situ conservation, strategic and targeted collection of germplasm would markedly increase the value of gene bank collections. Diversity of priority Czech CWR is concentrated in South Moravia, making this a particularly important CWR area for the country and for Europe.